MOHAMAD DJAZMAN’S RELIGIOUS-BASED PROGRESSIVE EDUCATION MOVEMENT - Ristianto, Eka Andy; Ali, Mohamad (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2018)
Mohamad Djazman is known as one of Muhammadiyah's active figures in the field of education. His concern for cadres and his humble, inspirational and progressive personality place him as a prominent figure among the cadres. only some literature has written or discussed its achievements or biographies. As a result, he is Jazman who is only known as the founder of UMS and IMM, without special recognition of other contributions. This study tries to explain the formulation of religious progressive education thought based on John Dewey's Progressive Education Theory and the prophetic religion of Mohammad Iqbal. The purpose of this study is to describe the progressive religious education developed by Mohamad Djazman. This research is classified as qualitative research in the form of library research using a philosophical-historical approach. The primary data source is the collection of Mohammad Djazman's writings in newspapers, magazines and books written during his lifetime. Sources of supporting data are other books that are relevant to the discussion and works written by other authors. The findings show that Mohamad Djazman's Progressive Religious Education concept is laying the foundation of progressive (charity) and religion (the Qur'an and Hadith) as the principle of progress so as to produce students who have scientific principles and scientific charity to answer the challenges of the times and spread Islam throughout the world.